The Potential Of Endophytic Bacteria From Rice Seeds To Control Bacterial Grain Rot (Burkholderia glumae) In Rice Plants - Mutiara Septu; Jumsu Trisno; Haliatur Rahma Rahma (Universitas Bangka Belitung, 2026)
Bacterial grain rot is one of the diseases caused by the bacterium Burkholderia glumae in the rice plant. This disease can cause a 40% loss in rice crop yield. One technique for controlling this disease is to use biological control agents, specifically endophytic bacteria. The study aimed to obtain endophytic bacterial isolates that can potentially suppress grain rot disease (B. glumae) in rice plants. The study was conducted experimentally using a completely randomized design (CRD) with 13 treatments and three replicates, each consisting of 2 experimental units. The treatments consisted of endophytic bacterial isolates BMI31, BMI33, ADI34, ADI35, ADI37, KKI35, KKI36, BI31, BI33, BI34, BI41, BPI41, a positive and a negative control. Endophytic bacteria were introduced into rice seeds and roots 21 days after sowing, while B. glumae was inoculated into rice plants at 45 days after sowing. The results of the study indicate that the endophytic bacteria with potential to control the development of bacterial grain rot disease in rice plants are isolates BMI33 and ADI35, with disease severity levels of 30.74%– 32.64% and effectiveness of 49.55–52.48%, AUDPC values of 293.99-351.95, and a percentage of disease development suppression effectiveness of 60.73%- 70.61%. The results show that endophytic bacterial isolates have the potential to become biological control agents.